408 Hyperkinetic and hypokinetic movement disorders – in pediatric clinical practice. (11th October 2021) - Barišić, N; Lehman, I; Bunoza, B; Chudy, D; Duranović, V; Jernej, B; Ahting, U; Haack, T; Prokisch, H; Willemsen, M
Abstract : To present heterogenous group of motor movement disorders of different etiology and clinical features. Medical history and clinical exam and assessment, MR neuroimaging, metabolic tests, molecular genetics, lumbar puncture and cerebrospinal fluid exam, antibodies to surface neuronal antigens, EEG monitoring, abdominal ultrasound were performed. Patients with autosomal dominant torsion dystonia DYT 6 (THAP1 gene mutation) and movement disorders caused by mutations in ATP1A3, SCN8A, CaCNa1, PANK2, POLG1 genes and acquired disorders: autoimmune (NMDAR) encephalitis, dyskinetic cerebral palsy, opsoclonus myoclonus ataxia will be presented as well as treatment response. MD can manifest alone or as part of complex phenotypes of different etiology. Considerable overlap of MD and seizures exists especially in patients with epileptic encephalopathies, ataxias and spasticity in whom clinical diagnosis can be more challenging.